2013
DOI: 10.1016/j.ajhg.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LARS2, Encoding Mitochondrial Leucyl-tRNA Synthetase, Lead to Premature Ovarian Failure and Hearing Loss in Perrault Syndrome

Abstract: The genetic causes of premature ovarian failure (POF) are highly heterogeneous, and causative mutations have been identified in more than ten genes so far. In two families affected by POF accompanied by hearing loss (together, these symptoms compose Perrault syndrome), exome sequencing revealed mutations in LARS2, encoding mitochondrial leucyl-tRNA synthetase: homozygous c.1565C>A (p.Thr522Asn) in a consanguineous Palestinian family and compound heterozygous c.1077delT and c.1886C>T (p.Thr629Met) in a nonconsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(179 citation statements)
references
References 32 publications
7
169
2
1
Order By: Relevance
“…The recombinant LARS2 p.Thr522Asn had a 9-fold loss of catalytic efficiency, consistent with yeast complementation studies that showed the yeast ortholog of LARS2 p.Thr522Asn retained partial function (Pierce et al 2013). Modeling of LARS2 on the E. coli leucyl-tRNA synthetase crystal structure indicates that Thr522 is located in the active site where the 3 0 end of the tRNA binds (Pierce et al 2013) (Fig. 2d).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The recombinant LARS2 p.Thr522Asn had a 9-fold loss of catalytic efficiency, consistent with yeast complementation studies that showed the yeast ortholog of LARS2 p.Thr522Asn retained partial function (Pierce et al 2013). Modeling of LARS2 on the E. coli leucyl-tRNA synthetase crystal structure indicates that Thr522 is located in the active site where the 3 0 end of the tRNA binds (Pierce et al 2013) (Fig. 2d).…”
Section: Discussionsupporting
confidence: 82%
“…LARS2 variants have previously been reported in association with sensorineural hearing loss and premature ovarian failure (Pierce et al 2013) in three siblings of Palestinian origin who were homozygous for the LARS2 p.Thr522Asn variant and a Slovenian child with compound heterozygous LARS2 p. Ile360fs*15 and p.Thr629Met variants (see Supplementary Table 3 for a comparison of phenotypes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of a few cohorts of 46,XX POI patients by means of high throughput techniques, such as comparative genomic hybridization array (array-CGH) and SNP array, has led to the identification of CNVs affecting several X-linked and autosomal loci with a possible role in female fertility (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Similarly, the recent application of whole-exome sequencing (WES) to a few POI multigenerational familial cases has succeeded in revealing rare single nucleotide variants affecting genes implicated in ovarian function (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). As already reported in other complex diseases characterized by a great genetic heterogeneity, it is likely that patients with POI may harbor multiple genetic variants.…”
Section: The Heterogeneous Manifestations and Multifactorial Origin Omentioning
confidence: 99%
“…DARS is also mutated in patients affected with leukoencephalopathy [82]. Resembling LBSL, there is another variety of leukoencephalopathy characterized by hypomyelination with brain stem and spinal cord involvement and leg spasticity, HBSL.…”
Section: Ars/ars2 Gene Mutation Causing Diseasesmentioning
confidence: 99%